The Development of Professional Zakat in the Digital Age; A Critical Analysis of the Determination of Professional Zakat for Content Creators in Indonesia - Hilmi Ridho; Afif Sabil; Khoirul Anwar; Nur Solikin; Hjh. Mas Nooraini binti Hj. Mohiddin (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2026)
The purpose of this study is to examine the appropriate zakat rate for content creators from the perspective of zakat law, evaluate its distributive justice, and formulate strategic measures to enhance zakat compliance among digital content creators. This research employs a normative-doctrinal legal approach based on library research and deductive reasoning. The primary legal materials consist of Konsensus Ulama Fatwa Indonesia: Himpunan Hasil Ijtima' Ulama Komisi Fatwa se-Indonesia VIII Tahun 2024, Potensi Zakat YouTubers, Influencers, and E-Commerce Affiliates di Indonesia 2024, and credible reports from online media concerning the latest income data of content creators across various digital platforms. Secondary legal materials include the opinions of contemporary Muslim scholars and previous studies on professional zakat. The findings reveal that income generated through social media activities constitutes zakatable wealth because it is earned regularly and, in many cases, exceeds the income of agricultural producers. Therefore, the Indonesian Council of Ulama (MUI) fatwa prescribing a professional zakat rate of 2.5% or 2.57% for digital content creators requires further reconsideration, as it raises concerns regarding equity when compared with the zakat obligations imposed on farmers. This study argues that the zakat rate applicable to digital content creators should be aligned with the provisions of agricultural zakat, namely 5% or 10%, depending on the production costs incurred in generating digital content. Furthermore, zakat should be calculated based on gross income rather than net income. To improve zakat compliance, zakat institutions should develop integrated digital payment systems connected to social media platforms, collaborate with prominent influencers to promote zakat awareness, and advocate for tax incentives for content creators who fulfill their zakat obligations. The study contributes to the ongoing development of professional zakat discourse in the digital era by recognizing content creation as a profession subject to zakat. It also underscores the importance of establishing zakat obligations for emerging professions that generate substantial income. Future research should explore the extent to which content creators comply with professional zakat requirements and identify factors influencing their compliance behavior.